CAMPAIGN ANALYSIS BEAUTY MOVES YOU AS A PROGRAM PUBLIC RELATIONS TO MAINTAIN WARDAH'S REPUTATION - Purnomo, Dhea Safitri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Wardah voiced the Beauty moves you campaign with the aim of motivating all women to carry out activities that are progressive and beneficial to those around them. So this research was carried out with the aim of finding out how the Beauty moves you campaign process, which is Wardah's public relations program, maintains its reputation. This research also aims to analyze the obstacles to the Beauty moves you campaign program and how they overcome these obstacles in building awareness of the target market. This research was conducted using the concept of a communication campaign model. This campaign model has several elements that describe how the effectiveness of a campaign carried out by public relations is conveyed to the audience. The effectiveness of the distribution of this campaign is directed at the form of reputation captured by the audience based on 4 company reputation assessments. This research uses a qualitative method with a descriptive approach. With the results, it was found that Wardah's public relations had succeeded in making changes in social behavior in accordance with the expectations of the Beauty moves you campaign through various media channels so that there was continuity in the expected effect in assessing Wardah's reputation. Keywords: Public relations campaign, Brand Reputation, Wardah, Beauty moves you